The Influence of Changing Cerebral Blood Flow on Temperature Distribution by Opto-thermal Simulation - Kuroda, Kagayaki; Washio, Toshikatsu; Matsumae, Mitsunori; Arafune, Tatsuhiko; Suzuki, Shiho (Transactions of Japanese Society for Medical and Biological Engineering, 2020)
Laser induced thermal therapy (LITT) is a new therapy for brain tumors based on optics and heat transfer.A heating region is determined by light propagation and heat transfer in LITT.Both physical phenomena can be represented by parabolic partial differential equation. A temperature distribution in living tissue can be predicted by solving the equation.A subject is to be carried heat away by blood flow in LITT. Generally speaking, it is known that increased blood perfusion decreases temperature in living tissue (JOMA 100.5-6 (1988): 655-667). It is easily assumed that laser irradiation is going to bring a localized temperature increasing. However, it is too difficult to grasp the temperature distribution in living tissue because of a lack of information about blood flow by localized heating, In this study, it is reported that a difference of the temperature distribution due to a difference of blood perfusion using opto-thermal numerical simulation.